Pengembangan Mobile Learning KORS pada Materi Fungsi Komposisi dan Invers untuk Melatih Kemampuan Berpikir Kritis - Siregar, Alfi Syahrin; Listiawan, Tomi (Jurnal Tadris Matematika, 2023)
Technology that continues to develop requires teachers to continue to innovate in presenting quality learning media. Mobile learning is a medium that can be used in learning because of the ease in the process of using it anywhere and anytime. On the other hand, critical thinking is a very important ability in mathematics. Through critical thinking skills, students are required to be able to generate thoughts and choose the right steps to solve a problem. However, the results of the field study show that students' critical thinking skills in material on compositional and inverse functions are still very low. This study aims to develop mobile learning named KORS to train students' critical thinking skills in the matter of compositional and inverse functions. This type of research is development research with the ADDIE model. The subjects of this study were practitioners and six high school students. In collecting data, assessment instruments were used by media experts and material experts, as well as student and teacher response questionnaires. The results of this study obtained KORS mobile learning media that were feasible to use with a percentage of 79% from media experts and 78.67% from material experts. The practicality of the media from the teacher's assessment obtained a percentage of 83.33% and based on the results of small-scale trials obtained a student response questionnaire percentage of 82.67%.